Secure and efficient two-party ECDSA signature scheme - Jing WANG; Libing WU; Min LUO; Debiao HE (Tongxin xuebao)
To solve the easy disclosure of signature private key and excessive concentration of signature rights, a secure and efficient two-party ECDSA signature scheme was proposed for the blockchain based network trading systems.By pre-computing one-time pad Beaver’s triple, and utilizing the Beaver’s triple based secure two-party multiplication technology, some computationally intensive homomorphic encryption operations and oblivious transfer operations with high communication overhead were effectively avoided, and thereby an efficient two-party ECDSA signing was realized, which could ensure that the two signing parties output valid ECDSA signature without reconstructing the complete private key.The proposed scheme was proved to be provably secure under the hybrid model of the universally composable framework.Theoretical analysis and simulation results demonstrate that the proposed scheme has significant advantages in terms of signing efficiency and bandwidth requirements when compared with the existing two two-party ECDSA signature schemes.